Lattice parameters of austenite and martensite during transformation for Fe–18Ni alloy investigated through in-situ neutron diffraction. (15th May 2023) - Gong, Wu; Harjo, Stefanus; Tomota, Yo; Morooka, Satoshi; Kawasaki, Takuro; Shibata, Akinobu; Tsuji, Nobuhiro
Abstract: Martensitic transformation is accompanied by the generation of microscale and macroscale internal stresses during cooling below the martensitic transformation start temperature. These internal stresses have been determined through X-ray or neutron diffraction, but the reported results are not consistent, probably because the measured lattice parameter is influenced not only by the internal stress but also by several factors, including solute elements and crystal defects. Therefore, in-situ neutron diffraction combined with dilatometry measurements during martensitic transformation and subsequent cyclic tempering were performed for an Fe–18Ni alloy. The phase strains calculated by lattice parameter variations show that a hydrostatic compressive strain in austenite and a tensile strain in martensite arose as the martensitic transformation progressed during continuous cooling or isothermal holding. However, the phase stresses of austenite and martensite estimated from these strains failed to hold stress balance law when dense crystal defects involved in the processes. After these crystal defects were removed by appropriate tempering, the stress balance law held well. Meanwhile, the phase stresses of austenite and martensite were changed to opposite, revealing their true identity. Furthermore, the lattice parameter of quenched full martensite and the specimen diameter were both decreased by tempering, demonstrating that there is a direct correlation among lattice parameter, specimen volume and dislocation density. As a result, various crystal defects in austenite and martensite, introduced by plastic accommodation, were suggested to affect their lattice parameters and then their phase stresses. Graphical abstract: Image, graphical abstract